A duplex connection can further illuminate G-quadruplex/crystal violet complex. Issue 13 (24th January 2019) - Wang, Shuang; Zhao, Jiahui; Lu, Shasha; Sun, Jian; Yang, Xiurong
Abstract : A duplex connection can distinctly enhance the fluorescence of G-quadruplex/crystal violet, which also was used in target DNA detection. Abstract : Duplex-connected G-quadruplex (dsG4) has a more evident promotion of the fluorescent emission of crystal violet than pure G-quadruplex (G4), which is firstly found and investigated systematically using fluorescence spectra, circular dichroism, and density functional theory. This new phenomenon also shows potential in application for target nucleic acid detection.